CORRELATION OF MANUS RADIOGRAPH IMAGE TEXTURE VALUE WITH BONE MINERAL DENSITY LUMBAR SPINE VALUE - Mulyono, Agus (Department of Physics, Maulana Malik Ibrahim State Islamic University of Malang, 2022)
Osteoporosis or bone loss is a chronic disease characterized by low bone mass accompanied by changes in micro-architecture of the bone and a decrease in the quality of bone tissue that can cause bone fragility, so that bones are easily cracked or even fractured. Osteoporosis is diagnosed by measuring bone mineral density using DXA (dual-energy X-rayabsorptiometry). Treatment with device this expensive and not widely available. So it is necessary to find an alternative method of detecting a cheap one. This study aims as an initial study to find an alternative way of early detection of osteoporosis by looking for the texture characteristics of the human bone. Sample in This study took 19 people with inclusion criteria including postmenopausal women who declared healthy, not broken bone and has no skeletal abnormalities since birth. Sample measured density mineral bone(BMD) or the degree of osteoporosis with DXA. Then an X-ray is done to get bone image. The stages of the research are: 1) preprocessing X-ray image of the human bone; 2) determine the value of the texture of the human bone image with gray level method co-occurrence matrix 3) test connection between the value of the human bone texture image with BMD lumbar spine. The results of the correlation test show that there is correlation between the value of human bone texture and BMD of the lumbar spine to characterize variance and significantly statistics (P0.05).